IMPLEMENTASI AKAD PESANAN BARANG PADA KONVEKSI CINTA COLLECTION PERSPEKTIF HUKUM EKONOMI SYARIAH : (Studi Kasus di Desa Tamanan Barat Kecamatan Tamanan Kabupaten Bondowoso). - Wardatul Imamah (LP3M KH Yazid Karimullah Institute, 2021)
The problem in this research is how when there is a discrepancy between ordered goods that have been made in the practice of istishna’ contract at the Cinta Collection Convection Tamanan, Tamanan District, Bondowoso Regency. What is the view of sharia economic law on the implementation of the order contract at the Cinta Collection Tamanan convection, Tamanan District, Bondowoso Regency. The type of research method used is field qualitative research with a qualitative descriptive approach. Data collection techniques were carried out by observation, interviews and comments. To obtain these answers, researchers used primary and secondary data. Both data were analyzed using qualitative analysis methods. The order agreement mechanism is carried out in two ways, the first is to go directly to the seller/manufacturer of the clothing maker, the two orders can be made via telephone, the internet and via WA (whats app) with the specifications desired by the consumer (size, color, design, etc.). In addition, the order payment mechanism can be made on the spot or can transfer through a bank account by providing a down payment of 50% of the total price of the order as a binding certificate, and the remainder can be paid at the end when the consumer receives the ordered goods. The results of the study show that in carrying out the contract for ordering goods at the Cinta Collection convection, the pillars and conditions for a valid contract have been fulfilled, but there are several transactions that have not fulfilled the pillars and conditions or are considered to have violated the agreement of the transaction contract which can also be called default.